The F-MARC study on Ramadan and football: Research design, population, and environmental conditions - Leiper, J. B.; Maughan, R. J.; Kirkendall, D. T.; Bartagi, Z.; Zerguini, Y.; Junge, A.; Dvorak, J. (Journal of Sports Sciences, 2008)
Ramadan is a month of penance during which Muslims take food or drink only after sunset and before the sun rises. This fast can present a considerable challenge to the Muslim athlete. Sports performance in those who observe Ramadan and those who do not has not been formally compared. Four Tunisian junior football squads participated in the study, and it was the individual's choice whether they observed the Ramadan fast. In this study, 64 players fasted while 36 players did not. Players completed daily questionnaires on perception of training difficulty before and during Ramadan. Anthropometric data were recorded 3 weeks before Ramadan, during the second and fourth weeks of Ramadan, and into the third week after Ramadan. Performance tests (sprint, leg power, agility, aerobic endurance, football-specific skills) were also measured on these test days. Nutritional intake was recorded by recall three times during each phase of the study. Haematological and biochemical analyses were performed on a 7-ml blood sample taken from each participant on each of the test days. Sweat samples were collected during a training session in the third week of Ramadan, when heart rate was also measured. The data analyses are presented and discussed elsewhere in this issue.